Religious Identity and Social Integration: An Ethnographic Study of the Balinese Hindu Community in East Lampung - Anggi Novita Sari; Deni Miharja (Prodi Magister Sosiologi UIN Sunan Gunung Djati Bandung, 2026)
This study examines the process of social integration and the maintenance of religious identity of the Balinese Hindu community in Pematang Tahalo Village, Hamlet IV, Gunung Kerung, Jabung District, East Lampung Regency. Within a predominantly Muslim community, the Balinese Hindu community demonstrates the ability to adapt and build harmonious social relations without obscuring its religious identity. This study aims to understand the social, cultural, and religious mechanisms that shape interfaith relations in a multicultural environment. The method used is a descriptive qualitative approach using in-depth interviews, participant observation, and documentation. Key informants included traditional leaders, religious leaders, community administrators, and Balinese Hindu youth. Data analysis was conducted inductively, referring to the theories of religion as a cultural system (Geertz), social solidarity (Durkheim), and the social construction of religion (Asad). The results indicate that social integration is built through interfaith cooperation, mutual cooperation, and mutual respect. Religious traditions such as mass cremation (ngaben), temple odalan (puppet ceremony), and melasti (pilgrimage ceremony) reinforce collective identity, strengthen social solidarity, and promote local pluralism.